Experimental verification of the Brinkman equation around objects with various shapes in gas–solid stationary and fluidized beds. (March 2023) - Honda, Yuji; Saito, Shiori; Anzai, Tetsuya; Harada, Shusaku; Tsuji, Takuya; Washino, Kimiaki; Oshitani, Jun; Kajiwara, Hirokazu; Matsuoka, Kei
Abstract: Experimental verification of Brinkman's theory, i.e., the permeation flow near an object immersed in a particle bed was conducted in this study. In order to examine the permeation flow and the fluidized state of media particles around an object in both stationary and fluidized beds, the air pressure near the object was measured by pressure sensors built in capsules with various shapes. The sensor system was fixed in the particle bed with various fluidization states and the pressure field around the object was measured. The effect of object shape was also examined by using the variously-shaped capsules, such as spherical, disk-like and cylindrical ones. The experimental results showed that the pressure around the object varies greatly with object shape. The permeation flow around the object in the particle bed was estimated by comparison with theoretical solutions. The pressure near the object in the stationary particle bed was quantitatively in agreement with the Brinkman theory, while the pressure in the fluidized bed fluctuated periodically. The experimental results suggested that the floating–sinking motion of objects in a gas–solid fluidized bed depends on the object shape and is greatly influenced by the instantaneous pressure variance near the object, rather than the averaged pressure gradient.